Observations on the pell proceedings - Lucas, Brian (The Australasian Catholic record, 2021)
Review(s) of: Observations on the pell proceedings, by Frank Brennan, Cleveland, QLD: Connor Court, 2021, pp. 160, paperback, $29.95.